Brand development of an educational institution - Myroshnyk, T. O. (WSEH, 2025)
Brand development in the educational sector is a strategic process aimed at creating a distinctive identity and strengthening the competitive position of an institution. It involves the integration of marketing communications, reputation management, and value-based positioning to attract students, faculty, and partners. A well-structured brand strategy enhances visibility, builds trust, and fosters long-term loyalty among stakeholders. By emphasizing academic excellence, innovation, and social responsibility, brand development contributes to sustainable growth and international recognition of the institution.
Keywords: brand development; educational institution; strategic positioning; reputation management; marketing communications; stakeholder loyalty; academic excellence; sustainable growth